Job Satisfaction Analysis on Employee Performance at the Office of the Ministry of Religion of North Sumatra - Muhammad Akram Al-musthaliqi; Sri Sudiarti (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effectiveness of employee performance at the office of the Ministry of Religion of the city of Makassar. This study is a quantitative description with a population of all employees of the Makassar City Ministry of Religion, amounting to 101 people. Sampling was carried out using a simple sampling technique (Simple Random Sampling), so that the number of samples that could be used in this study was 30 percent of the total 101 people, so the number of samples was 30 people. Data was collected through observation, questionnaires, interviews and documentation techniques. The data collected is presented through a frequency table and processed through a scoring technique. The results showed that the performance of employees at the office of the Ministry of Religion of the city of Makassar was classified as effective, based on the aspects; 1) quality of work, 2) punctuality, 3) initiative, 4) ability to complete work